2020
DOI: 10.1002/cssc.202002833
|View full text |Cite
|
Sign up to set email alerts
|

A Divergent Paired Electrochemical Process for the Conversion of Furfural Using a Divided‐Cell Flow Microreactor

Abstract: Furfural is a prominent, non‐petroleum‐based chemical feedstock material, derived from abundantly available hemicellulose. Hence, its derivatization into other useful biobased chemicals is a subject of high interest in contemporary academic and industrial research activities. While most strategies to convert furfural require energy‐intensive reaction routes, the use of electrochemical activation allows to provide a sustainable and green alternative. Herein, a disparate approach for the conversion of furfural i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 52 publications
(89 reference statements)
0
29
0
Order By: Relevance
“…Previous studies reported that furfural electrooxidation can generate HCOOH. 27,44 Impressively, the selectivity of HCOOH reached over 97%, while record-high FE (98.2%) and selectivity (93.1%) of HFO were also achieved at an optimal potential of 2.45 V vs NHE in our system (Figure 4a). The cycling performance testing proved the excellent catalytic stability of meso-PA/PmPD/GO in the oxidation of furfural to HFO (Figure 4b).…”
Section: ■ Results and Discussionmentioning
confidence: 75%
“…Previous studies reported that furfural electrooxidation can generate HCOOH. 27,44 Impressively, the selectivity of HCOOH reached over 97%, while record-high FE (98.2%) and selectivity (93.1%) of HFO were also achieved at an optimal potential of 2.45 V vs NHE in our system (Figure 4a). The cycling performance testing proved the excellent catalytic stability of meso-PA/PmPD/GO in the oxidation of furfural to HFO (Figure 4b).…”
Section: ■ Results and Discussionmentioning
confidence: 75%
“… Schematic representation of a divided‐cell flow microreactor design using an ion‐exchange membrane to separate the anodic and the cathodic electrolysis half‐cells. Reproduced with permission from reference [46] . Wiley 2021.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, it often suffers from a series of drawbacks in batch which lead to long reaction times as well as intricate conditions and side-products. The main drawbacks of electrochemistry can be in part mitigated under continuous flow conditions, as highlighted by seminal contributions from the Noël and Kappe groups, including for the preparation of APIs and relevant scaffolds [51][52][53][54][55][56][57][58]. An exemple from Noël's group is illustrated hereafter, where the authors provided an unprecedented continuous electrochemical protocol for upgrading biobased furfural 43 simultaneously into three industrially relevant molecules: Fig.…”
Section: Flow Chemistrymentioning
confidence: 99%